ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG GO PUBLIC DI BURSA EFEK INDONESIA PERIODE 2018 – 2021 - Silalahi, Donalson; Situmorang, Hesti Wahyuni; Purba, Saut; Sitompul, Pandapotan (LPPM Universitas Katolik Santo Thomas Medan, 2023)
The study was to examine the effect of Return on Equity, Return On Asset, Earning Per Share, and Debt to Equity Ratio on stock prices in Manufacturing companies that Go Public on the Indonesia Stock Exchange. This study uses secondary data, such as company financial reports and company performance summary reports taken from IDX with a population of 161 manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2021 and the number of samples taken based on the simple random sampling method is 61 manufacturing companies with a total of 61 data. The data was analyst using the SPSS 25 program. The t test results show ROE (0.916>0.05) which partially has no significant effect on stock prices, ROA (0.982>0.05) partially has no significant effect on stock prices, EPS (0.011 <0.05) partially has a significant effect on stock prices, and DER (0.321>0.05) partially has no significant effect on stock prices. The F test results show that ROE, ROA, EPS, and DER (0.001 <0.05) simultaneously have a significant effect on stock prices. Suggestions for investors should look at the company's EPS before making a decision, the company is expected to be able to increase the company's EPS value, and future researchers are expected to increase the number of samples to get comprehensive results and also add variables